(untitled) (World Bulletin of Public Health, 2022)
To evaluate the nurses’ / midwifes’ practice regarding managements of breastfeeding disorders among women during lactation. Methods: A cross-section design. The study was conducted in Holy Karbala City. A probability sample consisted of (27) nurses / Midwifes. The instrument validity was determined through content validity, by a panel of experts. Reliability of the instrument was determined through pilot study. Analysis of data was performed through the application of descriptive statistics) and inferential statistics. Results: The results of the study indicated that the majority of nurses midwifes who participated in the study were between the ages of (35 - 41) years and accounted (74.1 %).In addition, the study sample had a higher percentage of married nurses(74.1 %). There is no statistically significant difference between the study sample in terms of (age, marital status, residence, and level of education, Experience years, Training courses, self-education, and sources of self-education). Conclusion: There is a significant relationship between nurses’ and midwifes’ practice about breastfeeding disorders and its management and their age group, marital status, education level, years of hospital experience, and source of self-education during the testing period